(untitled) (Iranian Journal of Kidney Diseases, 2014)
Chronic kidney disease (CKD) is an emerging worldwide epidemic but few data are available in African populations. This study assessed prevalence of CKD in adults living Saint-Louis, northern Senegal. In a population-based survey between January and May 2012, 1037 adults living in Saint-Louis were assessed. Sociodemographical, clinical, and biological data were collected during household visits. Glomerular filtration rate was estimated using the 4-variable Modification of Diet in Renal Disease equation. Factors associated with CKD were identified by multivariate regression analysis. The mean age of participants was 47.9 ± 16.9 years. The majority of the participants lived in urban areas (55.3%) and had school education (65.6%). The overall prevalence rates of hypertension, diabetes mellitus, and obesity were 39.1%, 12.7%, and 23.4% respectively. Prevalence of CKD was 4.9% (95% confidence interval, 3.5% to 6.2%) and 0.9% had an estimated glomerular filtration rate less than 30 mL/min/1.73 m2. Before the study, 23% of the patients were aware of their disease. In multivariable logistic analysis, presence of CKD was significantly associated with hypertension and age. This study shows that CKD is frequent in adult population of Northern Senegal. A kidney health program is urgently needed to reduce the disease burden in both urban and rural areas.